Visualization of Endolymphatic Hydrops in Patients With Unilateral Idiopathic Sudden Sensorineural Hearing Loss With Four Types According to Chinese Criterion - Qin, Huan; He, Baihui; Wu, Hui; Li, Yue; Chen, Jianyong; Wang, Wei; Zhang, Fan; Duan, Maoli; Yang, Jun (Frontiers in Surgery, 2021)
Objective: The aim of this study is to evaluate the possible value of endolymphatic hydrops (EH) in patients with unilateral idiopathic sudden sensorineural hearing (UISSNHL) with four types according to audiometry. Methods: 72 patients (40 men and 32 women; age range, 28-78 years; mean age: 50.0±12.9 years) with UISSNHL were admitted retrospectively into this study. Based on the pure tone audiometry before treatment, the hearing loss of all these patients were categorized into 4-types: low-frequency group (LF-G), high-frequency group (HF-G), flat group (F-G) and total deafness group (TD-G). The average time from symptom onset to the first examination was 6.9±4.4 days (1-20 days). 3D-FLAIR MRI was performed 24h after intratympanic injection of gadolinium (Gd) within 1 week after the UISSNHL onset. The incidence of EH in the affected ears based on four types of hearing loss were analyzed using the Chi-square test and the possible relationship with vertigo and prognosis were also assessed. Results: 11 of 21 patients (52.4%) in the LF-G had the highest EH positive rate, followed by 18.2% in the HF-G, 11.8% in F-G, and 17.4% in TD-G. The significant difference was found in the four groups (P = 0.018). The EH rate of LF-G was statistically significantly higher than that of F-G and TD-G (P = 0.009, P =0.014), respectively. After valued by the volume-referencing grading system (VR scores), the EH level was represented by the sum scores of EH. In LF-G, no statistically significant difference was found in the prognosis of ISSNHL patients between with EH group and no EH group (P = 0.586). The symptom “vertigo” did not correlate with EH and prognosis. Conclusions: EH was observed in UISSNHL patients by 3D-FLAIR MRI. EH may be responsible for the pathology of LF-G but not related to prognosis. It might be meaningless to assess EH in other hearing loss types which might be more related to the blood-labyrinth disfunction.